2003
DOI: 10.1097/00004872-200301000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Importance of imidazoline-preferring receptors in the cardiovascular actions of chronically administered moxonidine, rilmenidine and clonidine in conscious rabbits

Abstract: The greater effect of efaroxan compared to the alpha(2)-adrenoceptor antagonist 2-MI suggests that the hypotension induced by chronic subcutaneous administration of moxonidine, rilmenidine and clonidine is mediated predominantly via an action on central imidazoline receptors. Furthermore, all agents showed a propensity to produce rebound hypertension with imidazoline receptor blockade. However, only clonidine showed a rebound phenomenon when challenged by acute central alpha(2)-adrenoceptor blockade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The dose was chosen to give a near maximum effect based on earlier dose-response studies with chronic administration to normotensive animals [29]. Control RSNA and HR baroreflexes were evoked as described earlier.…”
Section: Protocol For Chronic Rilmenidine Treatmentmentioning
confidence: 99%
“…The dose was chosen to give a near maximum effect based on earlier dose-response studies with chronic administration to normotensive animals [29]. Control RSNA and HR baroreflexes were evoked as described earlier.…”
Section: Protocol For Chronic Rilmenidine Treatmentmentioning
confidence: 99%
“…We conclude that hypertension in BPH/2J is likely to arise from sympathetic activity driven from regions other than the RVLM. Previous studies have shown that vagal excitatory effects become less prominent with chronic treatment [27,41] likely due to central a 2 -adrenoceptors desensitization [38]. Thus, to avoid these and other acute effects on the heart [18], as well as other peripheral actions of rilmenidine [42], the main focus of the present study involved determining the central sympatholytic hypotensive effects by central infusion of rilmenidine.…”
Section: Discussionmentioning
confidence: 99%
“…These doses were effective chronically as determined previously (Parkin et al, 2003). Moxonidine infusions were directly preceded by an initial 280 μg/kg intravenous bolus due to its slow onset of action.…”
Section: Methodsmentioning
confidence: 99%